Evaluating the RELM Test Results - Michael K. Sachs; Ya-Ting Lee; Donald L. Turcotte; James R. Holliday; John B. Rundle (International Journal of Geophysics)
We consider implications of the Regional Earthquake Likelihood Models (RELM) test results with regard to earthquake forecasting. Prospective forecasts were solicited for M≥4.95 earthquakes in California during the period 2006–2010. During this period 31 earthquakes occurred in the test region with M≥4.95. We consider five forecasts that were submitted for the test. We compare the forecasts utilizing forecast verification methodology developed in the atmospheric sciences, specifically for tornadoes. We utilize a “skill score” based on the forecast scores λfi of occurrence of the test earthquakes. A perfect forecast would have λfi=1, and a random (no skill) forecast would have λfi=2.86×10-3. The best forecasts (largest value of λfi) for the 31 earthquakes had values of λfi=1.24×10-1 to λfi=5.49×10-3. The best mean forecast for all earthquakes was λ̅f=2.84×10-2. The best forecasts are about an order of magnitude better than random forecasts. We discuss the earthquakes, the forecasts, and alternative methods of evaluation of the performance of RELM forecasts. We also discuss the relative merits of alarm-based versus probability-based forecasts.